CULTIVATION OF CATFISH WITH BIOFLOK METHOD ON CONVENTIONAL CATFISH FARMERS - Ary Kiswanto Kenedi; Rita Synthia; Cut Rafika Firdaus (Global Science Society, 2022)
Catfish farming training was carried out by catfish farmers in Meurandeh village. This training aims to increase catfish production by using the biofloc method. Catfish farming with a biofloc system is a system for raising catfish in a different way than usual, namely by growing micro-organisms whose function is to process waste from the cultivation itself which then turns into small lumps, and these lumps have benefits as natural food or feed for fish. The biofloc method is considered effective and can increase the productivity of catfish and also obtain fish with a larger weight and 20% weight and a faster harvest period, which is about 2.5 months (20%) than the usual method. The production of catfish from 4000 tails produces approximately 3000 fish with a weight of 96-110kg.